How do vulnerable road users look at road safety? International comparison based on ESRA data from 25 countries. (May 2019) - Torfs, Katrien; Meesmann, Uta
Highlights: Safety culture of vulnerable road users is assessed using ESRA-data (25 countries). Vulnerable road users report more crashes and feel less safe than car drivers. Pedestrians who feel very safe in traffic report less headphone use. Cyclists who feel very unsafe in traffic report more often to wear a helmet. Reliable international comparisons can be made based on ESRA-data. Abstract: The overall aim of the ESRA project is to provide scientific support to road safety policy by generating comparable national data on the current road safety situation. The first ESRA survey was conducted online using representative samples (N = 1000) of the national adult populations in 25 countries across the world. The field work was carried out in two waves: (1) June/July 2015, and (2) November 2016. In total, the first ESRA1 survey covers almost 27, 000 respondents, among which roughly 21, 000 were identified as vulnerable road users. Vulnerable road users such as pedestrians, cyclists, or motorcyclists suffer the most severe consequences in road crashes with other road users, because they cannot protect themselves against the speed and mass of the other party. Given their high vulnerability, these types of road users are of special interest to policy makers. The objective of this paper is to present the ESRA1 results regarding the safety attitudes of vulnerable road users. Special attention was given to 'road crash involvement', 'safety feeling', and 'self-reported unsafe traffic behavior' (i.e., the use of headphone and (motor)cycle helmet). Results show that vulnerable road users were more involved in road crashes compared to car drivers and that they feel less safe. Pedestrians feel safer in traffic compared to other types of vulnerable road users. Logistic regression models show that the use of headphones while walking and cycling is associated with gender, age, and support of policy measures. The use of a (motor)cycle helmet is associated with age and support of policy measures. The ESRA project has shown the feasibility and the added value of joint data collection by a network of road safety organizations. The intention is to extend the ESRA survey to an increasing number of countries and to repeat it on a triennial basis.